A Design of a Congestion Control Scheme Based on Multichannel in Wireless Sensor Networks. (1st September 2013) - Park, Siyong; Hwang, Sunmyung
Abstract : We propose a congestion control scheme on wireless multichannel sensor networks. The proposed congestion control scheme consists of a congestion detection strategy and two cases of congestion control strategies. The congestion detection strategy modeled in the Morkov chain provides two thresholds that can detect two congestion conditions, or light and heavy congestion conditions. The two congestion control strategies consist of a weak congestion control strategy that can control light congestion and a strong congestion control strategy that can control heavy congestion. In addition, the proposed congestion control scheme assigns a priority to a received packet according to their transmission distance, and it differentiates the number of useable channels when congestion occurs. We can reduce energy consumption due to retransmission because packets received from long distance can use more channels in the proposed scheme.